2020
DOI: 10.1177/0271678x20938137
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal salvinorin A improves neurological outcome in rhesus monkey ischemic stroke model using autologous blood clot

Abstract: Salvinorin A (SA) exerts neuroprotection and improves neurological outcomes in ischemic stroke models in rodents. In this study, we investigated whether intranasal SA administration could improve neurological outcomes in a monkey ischemic stroke model. The stroke model was induced in adult male rhesus monkeys by occluding the middle cerebral artery M2 segment with an autologous blood clot. Eight adult rhesus monkeys were randomly administered SA or 10% dimethyl sulfoxide as control 20 min after ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Consistent with results from nonhuman animal research, many human trials have shown Salvinorin A inhalation produced no significant changes in heart rate, blood pressure, O 2 saturation and core temperature suggesting a safe physiological profile of SA (Johnson et al 2011;Mendelson et al 2011). A recent study demonstrating that intranasal SA improves neurological outcome in a rhesus monkey autologous clot ischemic stroke model is very encouraging (Wu et al 2020). Further studies are needed to evaluate mechanisms that were not investigated in the past and also the role of SA treatment in immune-regulation after ischemic stroke.…”
Section: Introductionsupporting
confidence: 56%
“…Consistent with results from nonhuman animal research, many human trials have shown Salvinorin A inhalation produced no significant changes in heart rate, blood pressure, O 2 saturation and core temperature suggesting a safe physiological profile of SA (Johnson et al 2011;Mendelson et al 2011). A recent study demonstrating that intranasal SA improves neurological outcome in a rhesus monkey autologous clot ischemic stroke model is very encouraging (Wu et al 2020). Further studies are needed to evaluate mechanisms that were not investigated in the past and also the role of SA treatment in immune-regulation after ischemic stroke.…”
Section: Introductionsupporting
confidence: 56%
“…Based on cerebral angiography at 3 h post ischemia, we only included 3 monkeys with a still occluded M1-segment of MCA. Blood samples were drawn from the saphenous vein at baseline and 3 h after stroke onset ( Wang et al, 2016 ; Wu et al, 2021 ). MRI scanning was performed on a Magnetom Trio MRI Scanner (3.0 T; Siemens AG, Siemens Medical Solutions, Erlangen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…MRI scanning was performed on a Magnetom Trio MRI Scanner (3.0 T; Siemens AG, Siemens Medical Solutions, Erlangen, Germany). MRI sequences and parameters were reported in our previous study ( Wang et al, 2016 ; Wu et al, 2021 ). Based on recent reports, DWI images obtained 1 day after ischemia were defined as “originally abnormal region” ( Nagaraja et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the rats with forebrain ischaemia had a significant amelioration of motor and cognitive functions following salvinorin A treatment [190]. More recently, acute intranasal administration of salvinorin A (25 µg/kg) in a stroke rhesus monkey model highlighted its therapeutic potential for stroke rescue as the drug significantly decreased the brain infarct volume and improved neurological outcomes, neuroprotective effects that were maintained for 28 days after the procedure [191].…”
Section: Neuroprotectionmentioning
confidence: 99%